Implicit and explicit memory after focal thalamic lesions. - Exner, C; Weniger, G; Irle, E (Neurology)
Background: Lesions of the thalamus interfere with cognitive functions mainly in the area of declarative learning and memory. Little is known about the role the thalamus plays in implicit learning.Objective: To study explicit and implicit learning and memory in subjects with thalamic lesions and to analyze the influence of lesion characteristics on cognitive performance.Methods: The authors studied the performance of 15 subjects with focal thalamic infarction or hemorrhage on a comprehensive neuropsychological test battery focusing on tests of explicit memory and learning of a nondeclarative motor skill. Subjects with thalamic lesions were compared to 15 healthy matched control subjects and to a clinical control group of 22 subjects who had sustained basal ganglia lesions.Results: Subjects with thalamic lesions showed well-preserved intellectual and executive functions but demonstrated deficits on measures of attention and psychomotor speed, explicit memory, and implicit visuomotor sequence learning. Lesion size in the thalamus was clearly related to subjects' long-term explicit memory performance. However, few of the neuropsychological deficits found seemed specific to the long-term neuropsychological outcome of focal thalamic infarctions. Subjects with lesions in the basal ganglia demonstrated similar deficits.Conclusions: Focal subcortical lesions in the thalamus and the basal ganglia lead to a similar profile of neuropsychological deficits. Lesions in the thalamus not only affect declarative memory but also interfere with nondeclarative motor skill learning.